The Archaeology of Fazzan Synthesis - Daniels, Charles (Society for Libyan Studies Monograph, 2003)
This book seeks to advance knowledge of human settlement and adaptation in the world's largest desert, the sahara. Previous studies focussed on the prehistoric phases but this study takes a wider historical and geographical perspective. It sets out to combine the results of several field campaigns, their histories and methodologies. We look at fieldwork, fortifications, funerary structures, irrigation, rock art and human occupation. The final summary looks at the current state of research and offers a platform for future investigations.